Street gangs yesterday and today - Haskins, James, 1941- (New York Hastings House, 1974)
A history of street gangs from colonial times to the present discussing why they have persisted, who joins them, what needs they satisfy, and what they have in common with establishment groups.
Bibliography: p. 141-143.
Keywords: Gangs -- United States -- History -- Juvenile literature